Surface Removal Enhances the Formation of a Porous Structure in Potato Starch. (10th May 2021) - Gonzalez, Ana; Wang, Ya‐Jane
Abstract: Native potato starch exhibits limited susceptibility to enzyme digestion and does not form a porous structure. This study investigates the impact of granule surface on starch susceptibility to amylases. Two levels of surface removal via chemical gelatinization of common corn and potato starches are prepared and subjected to digestion by α‐amylase or glucoamylase. The degree of digestion varies with the surface removal level and starch type. A porous structure is observed in potato starch after combining surface removal and digestion by amylases. However, the pores in the surface‐removed potato starches are not as homogeneous or enlarged compare with corn starch. The removal of dense and tightly packed crystallites on the granule surface is proposed to enhance the degree of binding and hydrolytic activity of both amylases in potato starch. This study provides direct evidence that surface structure hinders amylase digestion and the formation of a porous structure in potato starch. Abstract : Native potato starch granule does not produce a porous structure after enzyme digestion partly because of its dense surface structure. Surface gelatinization removes the tightly packed outermost layer of the granule, which results in increase digestion degree and the formation of a porous structure. Porous potato starch has potential as a delivery system because of its resistance to digestion.